Anaplastic lymphoma kinase 5A4 immunohistochemistry as a diagnostic assay in lung cancer: A Canadian reference testing center's results in population‐based reflex testing. Issue 22 (7th August 2019) - Fiset, Pierre O.; Labbé, Catherine; Young, Kelvin; Craddock, Kenneth J.; Smith, Adam C.; Tanguay, Jeffrey; Pintilie, Melania; Wang, Ri; Torlakovic, Emina; Cheung, Carol; da Cunha Santos, Gilda; Ko, Hyang‐Mi; et al.
Abstract : Background: The presence of anaplastic lymphoma kinase ( ALK ) rearrangement predicts response to ALK tyrosine kinase inhibitor (TKI) therapy. Fluorescence in situ hybridization (FISH) was the initial reference standard to detect ALK rearrangement, but immunohistochemistry (IHC) using D5F3 has gained acceptance as an alternative diagnostic method. ALK IHC assays using other ALK antibodies have also been used as screening methods, but data supporting their utility as diagnostic tests have not been widely reported. Methods: Data from reflexive clinical ALK IHC test using the 5A4 clone concurrent with epidermal growth factor receptor ( EGFR ) mutation testing were analyzed. ALK IHC results were reported as negative (−), equivocal, or positive (+), with equivocal or positive staining validated by FISH break‐apart probe testing. Treatment outcomes were reviewed for ALK IHC+ patients. Results: Between 2012 and 2015, 146 (2.5%) cases were reported as ALK IHC+, 188 (3.2%) were reported as equivocal, and 5624 (94.4%) were reported as ALK IHC−. Of the ALK IHC+ cases, 131/143(91.6%) were ALK FISH+. Excluding 6 cases in which FISH was inconclusive or not performed, the positive predictive value was 95.6%, and the negative predictive value was 100%. Most specimens (n = 5352 [89.6%]) were also successfully tested for EGFR . Clinical responses to ALK TKIs were noted in 49 ALK IHC+ patients, with a median progression‐free survival of 9.9 months. Conclusions: ALK 5A4 IHC can serve as a robust diagnostic test for ALK ‐rearranged lung cancer and is associated with treatment response and survival. Optimized tissue allocation resulted in high success rates of combined reflex EGFR and ALK testing. Abstract : A large dataset derived from routine clinical reflex anaplastic lymphoma kinase (ALK) testing performed at a Canadian reference lung biomarker testing center demonstrates that the ALK 5A4 laboratory‐developed test is effective as both a screening assay and diagnostic assay to detect ALK fusion in lung cancer patient samples. The testing protocol also minimizes specimen tissue wastage and allows for successful additional biomarker testing in a majority of samples.